2021
DOI: 10.1111/tbed.14180
|View full text |Cite
|
Sign up to set email alerts
|

A multipronged next‐generation sequencing metabarcoding approach unearths hyperdiverse and abundant dog pathogen communities in Cambodia

Abstract: Recent surveys in Southeast Asia, including Cambodia, have identified canine vector‐borne pathogens (VBPs), including those with zoonotic potential, as highly prevalent. The lack of veterinary care alongside the close association semidomesticated dogs have with humans in the region exacerbates these zoonotic risks. Nonetheless, the number of studies investigating such pathogens and the threats they pose to dog and human health is limited. Here, we utilize a next‐generation sequencing (NGS)‐based metabarcoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 157 publications
0
40
0
Order By: Relevance
“…Hence, coinfection with VBB is not uncommon, making accurate diagnosis even more complex ( 11 ). To alleviate these issues, diagnostic methods capable of accurately detecting and characterizing VBB coinfections in a time-effective manner are essential, particularly in regions where canine pathogen diversity is high, such as the tropics ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, coinfection with VBB is not uncommon, making accurate diagnosis even more complex ( 11 ). To alleviate these issues, diagnostic methods capable of accurately detecting and characterizing VBB coinfections in a time-effective manner are essential, particularly in regions where canine pathogen diversity is high, such as the tropics ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our identification of the haemotropic M. haematoparvum and M. haemocanis in Bosnian dogs, as well as A. platys , is also novel data that extends the known endemic geographical range of these canine VBPs. Although none of these pathogen species is associated with significant lethality in dogs, A. platys is the aetiological agent of infectious canine cyclic thrombocytopaenia, a disease known to exacerbate clinical signs in dogs when identified in the context of VBP coinfections (Gaunt et al., 2010; Huggins et al., 2022). In addition, haemotropic Mycoplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, direct transmission through bites and blood transfusion have also been described (Tasker, 2010; Willi et al, 2007). Few studies have investigated the occurrence of haemoplasmas in EA and SEA, and have reported high prevalence in community dogs (40%), stray cats (23% to 38%) and client‐owned cats (23%) and their fleas (34%) from Thailand (Assarasakorn et al, 2012; Do et al, 2020; Huggins et al, 2019; Kaewmongkol et al, 2017) as well as in free‐ranging dogs (~13%) from Cambodia (Huggins et al, 2021; Inpankaew et al, 2016).…”
Section: Introductionmentioning
confidence: 99%